ANALISIS ISI LAMBUNG IKAN BAUNG (Mystus nemurus C.V) DI PERAIRAN SUNGAI SIAK KECAMATAN RUMBAI PESISIR PROVINSI RIAU - I. M. Sinaga; Titrawani '; Yusfiati ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Baung fish is one of fishery resources, which has significant economic potential in RiauProvince. Study on gut content can provide basic information that can be done topreserve the population of baung fish. A study on gut content of baung fish in SiakRiver of Rumbai Pesisir District, Riau Province has been carried out from July toNovember 2012 and from March to August 2013. The objective of this study was toknow about the diet composition on gut contents of baung fish such as main, suplement,and additional food. The method used in this study was The Index of Preponderance byNatarjan dan Jingran cit. Effendie (2002). The results of this study revealed that baungfish is categorized as a carnivore. The main food of baung fish was Rasbora sp(IP 34,2%), and additional foods were shrimp (IP 2,1%), Scutigera sp (IP 1,8 %), andGrynidae sp (IP 0,1%).